Dual effects of digital technology on high quality development of road transportation in Heilongjiang Province China - Peng Li; Ke Chen; Lusheng Liu; Zhijia Hou; Dahong Yang; Huiji Zhang (Scientific Reports)
Abstract The profound advancement of digital transformation has fundamentally altered various sectors within urban environments, with road transportation being no exception. Digital technology is regarded as a key driver for achieving high quality development of road transportation (HQDRT) and building a leading transportation nation.However, existing research has not comprehensively elucidated the mechanisms through which the level of urban digital technology (UDTL) influences HQDRT, nor has it thoroughly explored the accompanying synergistic effects, especially within the context of the current revitalization strategy for Northeast China. This study employs panel data from 12 prefecture-level cities in Heilongjiang Province spanning from 2011 to 2022, utilizing econometric methods and a coupling coordination model to rigorously analyze the dual effects of UDTL on HQDRT. Additionally, kernel density estimation and geographic detectors are applied to investigate the temporal and spatial heterogeneity of the synergistic evolution between these two factors and their underlying driving forces. The results indicate that UDTL possesses a positive influence on HQDRT across various prefecture-level cities in Heilongjiang, and a significant synergistic relationship is observed between these variables. Further analysis reveals pronounced regional disparities in their collaborative development, exhibiting a typical core-periphery structure. Core cities demonstrate substantial regional spillover effects through technological accumulation and institutional innovation, whereas peripheral cities confront challenges associated with delayed synergistic evolution. Furthermore, the prefecture-level cities in Heilongjiang are gradually transitioning towards a multi-layered and multidimensional comprehensive development stage, as traditional single-factor driven models are increasingly inadequate to meet the complex collaborative development needs of UDTL and HQDRT. This research extends the boundaries of existing studies focused on the digital transformation of road transportation and provides valuable insights for promoting green and sustainable development within this sector.